Carbon stress causes earlier budbreak in shade‐tolerant species and delays it in shade‐intolerant species. Issue 3 (28th February 2023) - Piper, Frida I.; Fajardo, Alex
Abstract: Premise: Climate change may lead to C stress (negative C balance) in trees. Because nonstructural carbohydrates (NSC) are required during metabolic reactivation in the spring, C stress might delay budbreak timing. This effect is expected to be greater in shade‐intolerant than in shade‐tolerant species, owing to the faster C economy in the shade‐intolerant. Methods: We experimentally induced C stress in saplings of six temperate tree species that differed in their light requirements by exposing them to either full light or shade from summer to spring, then recorded the date of first budbreak for the individuals. Because the levels of C reserves that represent effective C stress may differ among species, we estimated the degree of C stress by recording survival during the experiment and measuring whole‐sapling NSC concentrations after budbreak. Results: Shade reduced NSC concentrations and increased the sugar fraction in the NSC in all species. In the shade, shade‐intolerant species had higher mortality and generally lower NSC concentrations than the shade‐tolerant species, indicating a trend for more severe C stress in species with faster C economy. In shade‐intolerant species, budbreak started earlier and proceeded faster in full light than in shade, but in shade‐tolerant species budbreak was delayed in full light. The effects of the light environments on budbreak were not greater in shade‐intolerant than in shade‐tolerant species. Conclusions: Our study reveals a correspondence between budbreak responses to light and the light requirements of the species. This finding confirms that C metabolism has a significant role in triggering budbreak and demonstrates that whether C stress accelerates or delays budbreak depends on the species' light requirements.